1978
DOI: 10.1080/0002889778507805
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of firefighters to toxic air contaminants

Abstract: A personal sampling apparatus for firefighters was developed to sample the fire atmosphere for CO, CO2, O2, NO2, HCI, HCN and pariculate content. Two fire companies made ninety successful sample runs during structural fires. CO presented a potential acute hazard and particulate concentrations were high. HCN was detected at low levels in half the samples. HCI was detected in only eight samples but on two occasions exceeded 100 ppm. CO2 and NO2 levels and O2 depression do not appear to represent significant haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Woodsmoke exposures have been associated with respiratory infections, COPD, impaired lung function, and lung cancer (Naeher et al, 2006). Occupational exposures to wood smoke occur among occupations such as charcoal production workers (Kato et al, 2004), urban firefighters (Gold et al, 1978;Guidotti and Clough, 1992), and wildland firefighters (Reinhardt and Ottmar, 2004;Naeher et al, 2006). An estimated 70-80,000 US workers are involved in wildland firefighting annually (Harrison et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Woodsmoke exposures have been associated with respiratory infections, COPD, impaired lung function, and lung cancer (Naeher et al, 2006). Occupational exposures to wood smoke occur among occupations such as charcoal production workers (Kato et al, 2004), urban firefighters (Gold et al, 1978;Guidotti and Clough, 1992), and wildland firefighters (Reinhardt and Ottmar, 2004;Naeher et al, 2006). An estimated 70-80,000 US workers are involved in wildland firefighting annually (Harrison et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A double or single thickness of cotton was mounted in an empty activated carbon cartridge. Two sample flow rates were tested, 20 lpm and 50 Ipm. Two chamber ventilation rates were tested, 325 lpm and 45 lpm.…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Investigators in this study reported potentially harmful levels of hydrogen chloride, sulfur dioxide, aromatic hydrocarbons (benzene), PAHs, aldehydes (formaldehyde), dioxins and furans, and isocyanates. Many more studies investigating fire fighter exposures during structural fires have been conducted [Gold et al 1978;Treitman et al 1980;Brandt-Rauf et al 1988;Jankovic et al 1991;Bolstad-Johnson et al 2000;Austin et al 2001]. High levels (in excess of STELs) of CO, formaldehyde, acrolein, hydrogen chloride, hydrogren cyanide, sulphuric acid, and hydrogen fluoride have been reported during knockdown of structural fires [Jankovic et al 1991].…”
Section: Isocyanatesmentioning
confidence: 99%